2014
DOI: 10.1017/s1478951513001259
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden in end-of-life care: Advanced cancer and final stage of dementia

Abstract: In end-of-life care for patients with dementia, due to significant levels of caregiver distress and burden symptoms, there is a need to support caregivers in the same way as is done for caregivers of cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…In the United States, there are over 15 million unpaid caregivers who collectively provide 17.9 billion hours of assistance to the estimated 5.3 million patients with Alzheimer's disease (AD) . There undoubtedly is a large amount of burden on the caregivers of dementia patients both personally and economically . It appears that caregiver burden is not only a first‐world issue, Pattanayak et al also describe a similar increasing concern regarding caregiver burden in India …”
Section: Introductionmentioning
confidence: 99%
“…In the United States, there are over 15 million unpaid caregivers who collectively provide 17.9 billion hours of assistance to the estimated 5.3 million patients with Alzheimer's disease (AD) . There undoubtedly is a large amount of burden on the caregivers of dementia patients both personally and economically . It appears that caregiver burden is not only a first‐world issue, Pattanayak et al also describe a similar increasing concern regarding caregiver burden in India …”
Section: Introductionmentioning
confidence: 99%
“…Of caregivers of cancer patients, 32% to 50.7% were shown to be significantly burdened . Several studies found an adverse effect of CB on mental health during caregiving .…”
Section: Introductionmentioning
confidence: 99%
“…19 Of caregivers of cancer patients, 32% to 50.7% were shown to be significantly burdened. 22,23 Several studies found an adverse effect of CB on mental health during caregiving. [24][25][26][27] However, only few studies have focused on the long-term effects on bereavement adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore several studies have compared the burden of family caregivers of patients with cancer (hereafter referred to in this paper as PWC) and those of persons with dementia (hereafter referred to as PWD) with various results. Some studies reveal that family caregivers of both groups experience a similar level of burden (Kim and Schulz, 2008 ; Costa-Requena et al , 2015 ). Other studies show that family caregivers of PWD (hereafter referred to as FCD) have a higher level of burden (Papastavrou et al , 2012 ) and experience more stress than those caring for PWC (hereafter referred to as FCC) (Sampson et al , 2016 ), although one study found the opposite (Harding et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%